2021
DOI: 10.3389/fendo.2021.680494
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Expressing Neurons in the Substantia Nigra Regulate Locomotion, and in The Ventral Tegmental Area Motivation and Feeding

Abstract: Leptin is an anorexigenic hormone, important in the regulation of body weight. Leptin plays a role in food reward, feeding, locomotion and anxiety. Leptin receptors (LepR) are expressed in many brain areas, including the midbrain. In most studies that target the midbrain, either all LepR neurons of the midbrain or those of the ventral tegmental area (VTA) were targeted, but the role of substantia nigra (SN) LepR neurons has not been investigated. These studies have reported contradicting results regarding moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Studies have identified the involvement of MC3Rs and MC4Rs in reward circuits. Antagonists acting on MC3Rs and MC4Rs result in alterations in reward behaviors and locomotor activity (de Vrind et al, 2021;Dunigan et al, 2021a). A reward is derived from sex behaviors and regions such as the NAc, CPu, and the VTA are involved in the reward circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified the involvement of MC3Rs and MC4Rs in reward circuits. Antagonists acting on MC3Rs and MC4Rs result in alterations in reward behaviors and locomotor activity (de Vrind et al, 2021;Dunigan et al, 2021a). A reward is derived from sex behaviors and regions such as the NAc, CPu, and the VTA are involved in the reward circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant expression of Lepr‐b was also detected in other brain regions such as the cerebellum, multiple thalamic nuclei, the cortex, hippocampus, and the ventral tegmental area (VTA) (Bjørbæk et al, 1998; Elmquist et al, 1998; Figlewicz et al, 2003; Mercer, Hoggard, Williams, Lawrence, Hannah, Morgan, et al, 1996; Mercer, Hoggard, Williams, Lawrence, Hannah, & Trayhurn, 1996). Highlighting the contribution of such extrahypothalamic neurons in energy homeostasis, recent reports have identified neuronal populations in the cerebellum regulating satiation (Low et al, 2021), neuronal circuits including the thalamus being partly involved in leptin's anorexigenic effects (Zhang et al, 2020), and LEPR‐expressing neurons in the VTA and substantia nigra involved in food reward, energy intake, and locomotion (de Vrind et al, 2021; Fernandes et al, 2015; Hommel et al, 2006).…”
Section: The Rise Of the Classic Leptin–melanocortin Modelmentioning
confidence: 99%
“…This gene is expressed in a variety of tissues, such as the hypothalamus, IVDs, cartilage, and bone. 122 , 123 , 124 , 125 , 126 What's more, it is an important marker of stem cells derived from the periosteum, mesenchymal stem cells and notochord derived cells, and has the characteristics of stem cells. It has been suggested that Lepr ‐expressing cells can differentiate into chondrocytes, fibroblasts, osteoblasts, and adipose cells.…”
Section: Conditional Ko Micementioning
confidence: 99%
“…The leptin receptor ( Lepr ) gene belongs to the obesity gene family, which encodes leptin receptor that recognizes and transports leptin. This gene is expressed in a variety of tissues, such as the hypothalamus, IVDs, cartilage, and bone 122–126 . What's more, it is an important marker of stem cells derived from the periosteum, mesenchymal stem cells and notochord derived cells, and has the characteristics of stem cells.…”
Section: Conditional Ko Micementioning
confidence: 99%